Severe Acute Respiratory Syndrome : a Clinical Guide. - Peiris, Malik (John Wiley & Sons, 2008)
Prompting the first WHO global health alert for over a decade, Severe Acute Respiratory Syndrome (SARS) was first recognised in South-East Asia in February 2003. With the causative agent now identified as a new strain of coronavirus, the medical world has gained important knowledge on the aetiology, clinical presentation, diagnosis, pathogenesis, epidemiology, disease treatment and infection control with amazing speed. Despite this, major gaps remain in our understanding - the race is on to develop new cures and effective vaccines, and the long-term impact on health, society and economics are.